2015
DOI: 10.1007/s10661-015-4892-9
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentrations and enzymatic activities in the functional zone sediments of Haizhou Bay, Lianyungang, Jiangsu, China

Abstract: Surface sediments were collected at 31 sites covering five functional zones of Haizhou Bay, Lianyungang, Jiangsu, China. Heavy metal concentrations and enzymatic activity of phosphatase and urease were determined on a dry-weight basis of sediments. Metal concentrations in sediments were comparable to the Chinese National Standard of Marine Sediment Quality and were as follows: Cu, 8.60-55.8 mg kg(-1); Zn, 107-384 mg kg(-1); Pb, 33.6-200 mg kg(-1); Cd, 0.24-2.57 mg kg(-1); Cr, 30.3-92.1 mg kg(-1); As, 12.9-110 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 35 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Similarly, it was shown that Cd had a distinct inhibitory effect on urease, acid phosphatase, and catalase activities (Mao et al 2015;Xin et al 2017). The enzyme activities decreased in the presence of heavy metals, which can interact with the enzyme-substrate complex and denature the enzyme or interact with active sites of proteins (Li and Liu 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, it was shown that Cd had a distinct inhibitory effect on urease, acid phosphatase, and catalase activities (Mao et al 2015;Xin et al 2017). The enzyme activities decreased in the presence of heavy metals, which can interact with the enzyme-substrate complex and denature the enzyme or interact with active sites of proteins (Li and Liu 2015).…”
Section: Discussionmentioning
confidence: 95%